(untitled) - María de los Angeles Ribas Antúnez; Blanca Girón; Iraima Monsalvez; Luis Morier; Gretel Acosta; Yahisel Tejero; Yanislet Cordero; Dainelyd Piedra (Memorias do Instituto Oswaldo Cruz, 2013)
Rabies is a neurotropic disease that is often lethal. The early diagnosis of rabies infection is important and requires methods that allow for the isolation of the virus from animals and humans. The present study compared a modified shell vial (MSV) procedure using 24-well tissue culture plates with the mouse inoculation test (MIT), which is considered the gold standard for rabies virus isolation. Thirty brain samples (25 positive and 5 negative by the fluorescent antibody test) obtained from different animal species at the National Institute of Hygiene Rafael Rangel in Caracas, Venezuela, were studied by the MIT and MSV assays. Nine samples (36%) were positive at 24 h, 10 (40%) were positive at 48 h and six (24%) were positive at 72 h by the MSV assay. With the MIT assay, 76% were positive at six days post inoculation and 12% were positive at 12 and 18 days post inoculation. One sample that was negative according to the MSV assay was positive with MIT on the 12th day. The MSV procedure exhibited a sensitivity of 96.2%, a specificity of 100%, a positive predictive value of 100% and a negative predictive value 80%. This procedure allowed for rapid rabies virus detection. MIT can be employed as an alternative method in laboratories without tissue culture facilities.